Insecticidal effects of wood vinegars produced from organic wastes on harmful almond leaf bee Cimbex quadrimaculata (Müller, 1766) (Hymenoptera: Cimbicidae) - Koç, İbrahim; Özgen, İnanç; Topdemır, Aykut; Güral, Yunus (My University, 2024)
In agricultural activities, there is an increasing need for organic products as alternatives to chemical pesticides. Wood vinegar (WV, pyrolysis liquid) from these alternative potential products is produced as a result of the carbonization process in which it is obtained from organic wastes together with useful products such as energy and biochar. This study was carried out to determine the insecticidal effects of WVs produced from broiler chicken litter and nutshells on the harmful almond leaf wasp Cimbex quadrimaculata Müller, 1766 (Hymenoptera: Cimbicidae). The study was carried out in an almond orchard in Diyarbakır (Eğil district) and Elazığ (Keban district) in the 2019-2021 production seasons. WV mixed solutions (1%, 3%, 5%, 7%, 10% and 25%) were applied with a back sprayer at the beginning and end of leafing in contaminated almond orchards. The effects of the applications were determined by impact and visual control methods on the 1st, 7th, 14th and 21st. In the analysis of the obtained data, first of all, normality test was performed. In the analysis of the obtained data, the Kruskal-Wallis test was applied. In conclusion; It has been determined that WV-added solutions have a insecticidal effect against harmful almond leaf bees, and the highest decrease in the number of larvae occurs at doses of 10% to 25%. It is important to test these vinegars in different locations with more detailed studies and to conduct detailed bioecological studies depending on the climatic factors and population ecology of the pest in terms of alternative control of the pest. The data of this study contain basic data for almond integrated pest management (IPM) studies.
Keywords: Almond; Insecticidal effect; Cimbex quadrimaculata; Alternative control; Wood vinegar (pyrolysis liquid)